Characterisation of breast lesions: comparison of digital breast tomosynthesis and ultrasonography - Pandya, Madhavi; Jain, Abhilasha (International Journal of Research in Medical Sciences, 2021)
Background: The main aim of the study was to characterize breast lesions using digital breast tomosynthesis and ultrasound and compare the detection and characterization of lesions between both the modalities. Methods: This was a cross-sectional, observational study that included 150 women who were screened with mammography followed by digital breast tomosynthesis and ultrasound for breast cancer. Patients approaching willingly for screening as per the inclusion criteria underwent mammography and digital breast tomosynthesis followed by ultrasonography. In lesion showing characteristics of malignancy biopsy correlation was done. Results: About half of the patients had type C tissue composition of the breast (50.67%). Most patients were of age between 35 to 44 years (46%). Malignant lesions were similarly detected by both the modalities. Almost all benign cases were also similarly diagnosed. Sensitivity and specificity of ultrasonography was 94.85% and 92%. Sensitivity and specificity for tomosynthesis was 91.86% and 88.24%. Combined testing showed 100% sensitivity, 97.8% specificity, 98.36% positive predictive value and 100% negative predictive value. Conclusions: Combining use of tomosynthesis and ultrasonography can make it possible to detect any small lesion, malignancy in its earliest stage (in situ) as well as few premalignant conditions like atypical ductal hyperplasia, as in few conditions there is possible sonography negative and mammogram positive calcifications are found.